Nanomaterials for Fuel Cell Catalysis - Ozoemena, Kenneth I.; Chen, Shaowei; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
Global experts provide an authoritative source of information on the use of electrochemical fuel cells, and in particular discuss the use of nanomaterials to enhance the performance of existing energy systems. The book covers the state of the art in the design, preparation, and engineering of nanoscale functional materials as effective catalysts for fuel cell chemistry, highlights recent progress in electrocatalysis at both fuel cell anode and cathode, and details perspectives and challenges in future research.
Electrochemistry fundamentals: nanomaterials evaluation and fuel cells -- Recent Advances in the Use of Shape-Controlled Metal Nanoparticles in fuel cell electrocatalysis -- Pt-Containing Heterogeneous Nanomaterials for Methanol oxidation and Oxygen Reduction Reactions -- Synthesis and Electrocatalysis of Pt-Pd Bimetallic Nanocrystals for Fuel Cells -- Integrated Studies of Au@Pt and Ru@Pt Core-Shell Nanoparticles by in situ Electrochemical NMR, ATR-SEIRAS, and SERS -- Recent Development of Platinum-based Nanocatalysts for Oxygen Reduction Electrocatalysis -- Enhanced Electrocatalytic Activity of Nanoparticle Catalysts in Oxygen Reduction by Interfacial Engineering -- Primary oxide latent storage and spillover for reversible electrocatalysis in oxygen and hydrogen electrode reactions -- Metal-organic frameworks as materials for fuel cell technologies -- Sonoelectrochemical Production of Fuel Cell Nanomaterials -- Direct Ethanol fuel cell on carbon supported Pt based nanocatalysts -- Direct Alcohol Fuel Cells: Nanostructured materials for the electrooxidation of alcohols in alkaline media -- Effects of Catalyst-Support Materials on the Performance of Fuel Cells -- Microbial fuel cell perspective and the application of nanomaterials.
Keywords: Electrochemistry; Nanochemistry; Catalysis; Electric power production; Energy storage; Electrochemistry; Nanochemistry; Catalysis; Electrical Power Engineering; Mechanical Power Engineering; Mechanical and Thermal Energy Storage